4;0. X=4,y=0 .x=0 не может так как под корень с -4 не имеет значение
А) а(х-2) -b(х-2)-с(х-2)=(а-b-с)(х-2)
б) (х-y)(2а-с)+2b(y-z)
<span>№2
1) (4,5-11,7)/(1,9+1,7) = -7.2/ 3.6= -2</span><span>
2) 139/4+(27,3*1/3-4,1):1/2-5/4</span> = 34.75 + 5/ 0.5 - 1.25= 34.75 +10 _1.25= 43.5 <span>
3) 441*362+441^2-441*303= </span>159 642+194 481-133 623=220 500
№3
<span>1) -m+2n
Если m=9,n=-6</span> , то -9+2*(-6)=-9-12=-21
<span>2)-3n^2-m^3
Если m=-4,n=5 , то-3*5^2-(-4)^</span>3=-75+64=-11
<span>3) m-n(m+n)
Если m=-3/5,n=-0.2 , то -(3/5)-(-0.2)*(-(3/5)+(-0.2))=-0.6+0.2*(-0.6-0.2)=
=-0.6-0.16=-0.76</span>
№4
<span>1)1.2(4y-3)-3(12+5y)= 4.8у-3.6-36-15у=-10.2у-39.6</span><span>
2)-5(3a-1)+(6-4a)2-3(2+a)=-15а+5+12-8а-6+3а=-20а-11
-20а=11 | : (-20)
а=-0.55
</span>